MALT1-Deficient Mice Develop Atopic-Like Dermatitis Upon Aging - Demeyer, Annelies; Van Nuffel, Elien; Baudelet, Griet; Driege, Yasmine; Kreike, Marja; Muyllaert, David; Staal, Jens; Beyaert, Rudi (Frontiers in Immunology, 2019)
MALT1 plays an important role in innate and adaptive immune signaling by acting as a scaffold protein that mediates NF-B signaling. In addition, MALT1 is a cysteine protease that further fine tunes proinflammatory signaling by cleaving specific substrates. Deregulated MALT1 activity has been associated with immunodeficiency, autoimmunity, and cancer in mice and humans. Genetically engineered mice expressing catalytically inactive MALT1, still exerting its scaffold function, were previously shown to spontaneously develop autoimmunity due to a decrease in regulatory T cells associated with increased effector T cell activation. In contrast, complete absence of MALT1 does not lead to autoimmunity, which has been explained by the impaired effector T cell activation due to the absence of MALT1-mediated signaling. However, here we report that MALT1 deficient mice develop atopic-like dermatitis upon aging, which is preceded by Th2 skewing, an increase in serum IgE, and a decrease in Treg frequency and functionality.